FUNDAMENTAL PRINCIPLE AND APPLICATIONS OF THERMAL ANALYSIS BY DIFFERENTIAL SCANNING CALORIMETRY IN PHARMACEUTICAL SOLID-STATE FORMULATIONS - Tipduangta, Pratchaya; Sirithunyalug, Jakkapan (Thai Bulletin of Pharmaceutical Sciences, 2018)
Differential scanning calorimetry (DSC) is an important thermal analysis technique which is frequently used in pharmaceuticals, especially in solid-state formulations. The development of Modulated Temperature Differential Scanning Calorimetry (MTDSC) which is an extension of conventional DSC, it employs a non-linear heating rate like a sine wave or seesaw which offers a remarkable advantage of deconvoluting the heat flow signal into reversing heat flow and non-reversing heat flow by using a Fourier transform mathematic deconvolution. MTDSC can separate non-reversible thermal events such as water evaporation or polymer relaxation from reversible thermal events (glass transition temperature). Consequently, it reveals hidden thermal events and improves the resolution of detecting a glass transition temperature. Additionally, this review also focuses on the applications of conventional DSC and MTDSC in pharmaceutical solid-state formulation development including identification of polymorphism of active pharmaceutical ingredients (APIs) and their thermodynamic properties, a study of the crystallization kinetics of APIs, assessment of the interaction between APIs and excipients, and characterization of solid dispersion formulations and the long-term stability of the amorphous drug in the formulations.